Corporate taxation and investment of multinational firms Evidence from firm-level data - Millot, Valentine (OECD Publishing, 2020)
This paper explores the effect of corporate taxes on the investment of multinational enterprises (MNEs), and whether this effect differs across MNE groups depending on their profitability rate. Firm-level analysis conducted on a cross-country panel of MNE entities confirms the earlier finding that MNE investment in a jurisdiction is negatively affected by effective corporate tax rate increases in that jurisdiction. The analysis also suggests that the tax sensitivity of MNE investment differs across entities belonging to different MNE groups, with a U-shape relationship between tax sensitivity and MNE group profitability. Entities belonging to groups with negative profitability or relatively high profitability rates are found to be relatively less sensitive than those belonging to groups with lower but positive profitability rates. For example, the estimated tax sensitivity of firms in MNE groups with a profitability rate above 10% is found to be nearly half the sensitivity of a firm in an MNE group with a profitability rate between 0% and 10%. This has implications with regard to the tax reform proposals currently under discussion by the OECD/G20 Inclusive Framework on BEPS, as this suggests that highly profitable MNE groups, which are more likely to be impacted by the proposals, may be less sensitive to taxes in their investment behaviour than the typical MNE.
Keywords: Finance and Investment; Taxation; Economics